Penerapan PTS Berbasis CBT untuk Mengurangi Limbah Kertas dari Lembar Soal dan Jawaban Peserta Didik - Wiliyanti, Vandan; Shidqha, Nur Haq (JURNAL ABDIMAS DOSMA (JAD), 2023)
Abstract : The implementation of the Middle Semester Assessment (PTS) using a computer or Computer Based Test (CBT) at SMAN 10 Bandar Lampung runs from the start of online learning until 2022 in the odd semester. The implementation of computer-based assessment in addition to being easy to apply is also able to reduce the use and waste of paper that comes from student question and answer sheets. With this, it is able to make schools healthy and environmentally friendly.